Using molecular markers to assess Streptococcusmutans variability and the biological risk for caries - Ivana Froede Neiva; Mônica Moreira; Renata Rodrigues Gomes; Debora Klisiowicz; Ricardo Lehtonen Rodrigues Souza; Vânia Aparecida Vicente (Universidade Estadual de Campinas, 2010)
Aim: To characterize the genetic variability of Streptococcus mutans isolates and to correlate this variability with different colonization profiles observed during dental caries in a sample of children. Methods: S. mutans samples were isolated from the saliva of 30 children with varying histories of dental caries, and they were characterized according to morphological and biochemical markers and the sequences of their 16S-23S intergenic spacer region. The genetic variability of the isolates was first assessed using Random Amplified Polymorphic DNA (RAPD) markers. Next, the isolates were differentiated by sequencing a specific region of the gene encoding the enzyme glucosyltransferase B (gtfB). Results: Characterization using RAPD markers uncovered significant genetic variability among the samples and indicated the existence of clusters, which allowed us to reconstruct both the origin and clinical history of the disease. By sequencing the 16S-23S intergenic region, it was found that all of the isolates belonged to the species S. mutans. Based on the genetic similarity of the isolates and pattern of amino acid variations identified by partial sequencing of the gtfB gene, base-pair changes were identified and correlated with different virulence patterns among the isolates. Conclusions: The partial sequencing of the gtfB gene can be a useful tool for elucidating the colonization patterns of S. mutans. As amino acid variations are likely to be correlated with differences in biological risk, molecular characterization, such as that described in this paper, could be the key for assessing the development of dental caries in children.